KD PROBLEM FOR A QUASILINEAR EQUATION OF AN ELLIPTIC TYPE WITH TWO LINES OF DEGENERATION - Rasulov, Haydar (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
The unique solvability of the KD problem for an equation of the elliptictype with two lines of degeneration is proved. The uniqueness of the solution to the KD problem is proved using the extremum principle for elliptic equations, and the existence of the method of contraction mappings.